Labour and Capital Under a Neoliberal Economic Model: Economic Growth and Demographic Crisis in Lithuania. Issue 9 (21st October 2018) - Lazutka, Romas; Juška, Arūnas; Navickė, Jekaterina
Abstract: This study investigates the split of national income between labour and capital in Lithuania and its distributional implications. It shows that the neoliberal economic development model embraced by Lithuania since regaining independence in 1991 produced significant economic growth. However, this growth was based on suppressing wages, keeping taxes on capital low and exporting cheap labour to the core EU countries. This resulted in high inequalities in income and wealth that have contributed to a deep socio-demographic crisis in the country. It is argued that in order to make Lithuanian capitalism socially sustainable, the neoliberal model of development needs to be reconsidered and modified.